PENTINGNYA MANAJEMEN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN USAHA KECIL MENENGAH - Hanung Eka Atmaja; shinta ratnawati (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2018)
National development is a continuous effort to improve the quality of people and society in Indonesia. Economic development that was originally oriented to the growth of large-scale industries shifted to economic development that was more emphasis on the populist economy. One of them through SMEs but many small industries or SMEs that can not grow one of them is the industri krupuk rambak  in Kendal because of the lack of ability of their MSDM so many businesses out of business. With the improvement of the quality of MSDM and also the role of government is expected to improve the knowledge and skills of entrepreneurs in terms of technology, facilities and infrastructure, capital and marketing.